SELF-CONFIDENCE AND ANXIETY IN STUDENTS WHO ARE DOING THESIS - Menik Tetha Agustina (STAH Dharma Sentana Sulawesi Tengah, 2023)
Students often experience excessive anxiety when completing their thesis. This is due to a lack of self-confidence in students. This research aims to see whether there is a relationship between self-confidence and anxiety in students who are doing their thesis. The respondents in this research were 74 students at Karangturi National University, Semarang, class of 2019. The sampling technique in this research was the Saturated Sample Technique. Research data was collected using two scales, namely the self-confidence scale and the anxiety scale. Data analysis uses the Product Moment Correlation Technique. From the results of this research, it was found that there was a negative relationship between self-confidence and anxiety in students who were taking their thesis with a correlation coefficient of -0.330 with a significance of 0.004 (p < 0.05), meaning that the higher the self-confidence, the lower the anxiety. Conversely, the lower self-confidence, the higher the anxiety